Epizootic pertussis focus of hamadryad baboons - A. Yu. Medkova; G. I. Karataev; Z. V. Shevtsova; A. Z. Matua; E. G. Semin; A. A. Amichba; L. N. Sinyashina; I. G. Kondzariya; V. S. Barkaya; Z. Ya. Mikvabia; A. L. Gintsburg (Журнал инфектологии, 2015)
The absence of an adequate experimental animal model makes difficult study of immunity against whooping cough and its pathogenesis. Experimental whooping cough reported by us earlier in pubescent non-human primates of the Old World was accompanied by specific clinical and laboratory marks in the absence of cough. The possibility of pertussis modelling while experimental whooping cough in impuberal hamadryad baboons was investigated. In the process of selection of monkeys for the further studies for perfecting of experimental model for pertussis research unexpectedly were detected specific pertussis antibodies in impuberal hamadryad baboons.The aim of the study: revealing of source of infection and transmission of pertussis to hamadryad baboons and investigation of response of antibody-positive impuberal hamadryad baboons to secondary contagion by B. pertussis bacteria while experimental infection.Results. 18 veterinary checked, somatically healthy hamadryad baboons of various gender managed in two neighboring cages. Specific pertussis IgM and IgG antibodies were found in blood serum of all the animals and one of the monkey keepers. By real-time PCR in nasopharyngeal swabs of the monkey keeper and three 7- and 9-month-old hamadryad baboons were registered single B. pertussis genom equivalents. Seropositive impuberal hamadryad baboons were experimentally challenged by virulent B. pertussis 475 strain. Quantity of B. pertussis genom equivalents and percentage of IgM and IgG antibodies in impuberal hamadryad baboons after experimental infection were detected. These results were comparable with such received after secondary experimental challenge of monkeys by B. pertussis. Humoral immuneresponse was characterized by booster effect and rapid B. pertussis elimination.Conclusion. The case of transmission of B.pertussis bacteria to hamadryad baboons by natural contagion and epizootic focus of pertussis in apery conditions were registered. In dynamics of immune response and level of bacterial load in experimentally infected impuberal and pubescent hamadryad baboons were not revealed significant differences. The possibility of asymptomatic B.pertussis transmission from man to monkey and from monkey to man without definitive spasmodic cough was reviewed. Pertussis research perspectives using experimental model of non-human primates of the Old World were marked.